2000
DOI: 10.1007/bf02492823
|View full text |Cite
|
Sign up to set email alerts
|

Study of volatile aroma components in young Tokaji Aszu wines by GC-MS

Abstract: Summary"Tokaji Aszu". is the most famous Hungarian wine type with a very delicious, unique aroma. Tokaji Aszu wines are produced from noble rotten grapes by a special vinification technology. In the last few years certain wineries have made an effort to introduce some changes into this traditional process. The present work examines the effect of different vinification technologies on some aroma components in one year old Aszu wines. The volatile aroma components were determined by gas chromatography-mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…[32] The aliphatic ketones 17-20 and 23 and the alcohol 22 have not previously been reported from nature, whereas the ketone 21 occurs in the essential oil of Ruta angustifolia. [33] The amide 12 has been identified in wines [34] and is also known as an alarm pheromone of cockroaches [35] and wasps [36][37][38] and a as volatile constituent of Nicotiana tabacum, which also contains 9.…”
Section: Discussionmentioning
confidence: 99%
“…[32] The aliphatic ketones 17-20 and 23 and the alcohol 22 have not previously been reported from nature, whereas the ketone 21 occurs in the essential oil of Ruta angustifolia. [33] The amide 12 has been identified in wines [34] and is also known as an alarm pheromone of cockroaches [35] and wasps [36][37][38] and a as volatile constituent of Nicotiana tabacum, which also contains 9.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research showed that while the terpene content typically decreases in these wines, numerous hydroxy-, oxo-, and dicarboxylic acid esters, acetals, and lactones form, which are present in lower concentrations or absent in normal wines. [58][59][60][61] The first research on the chemical nature of botrytized aroma character focused mainly on heterocyclic odoriferous compounds. One of the first compounds identified as a key odorant in these wines was sotolon (4,5-dimethyl-3-hydroxy-2(5H)-furanone), having a sweetish, caramel, or nut taste.…”
Section: Aroma Composition Of Botrytized Winesmentioning
confidence: 99%
“…Fortunately, most aroma and flavour compounds are volatile and procedures for their isolation from food samples have been established by taking advantage of this volatility. However, commonly used sampling methods such as steam distillation, solvent extraction, trapping of the volatiles on adsorbents or combinations of these methods with other techniques prior to chromatographic separation117 are very labour intensive. Using SPME combined with GC/MS (or GC/flame ionization detection (FID)), the disadvantages of these commonly used sample preparation methods can be avoided.…”
Section: Application Of Spmems In Various Fields Of Analytical Chemistrymentioning
confidence: 99%